Theological Meaning of The Munggahan Ramadhan Ritual in Bandung, West Java - Komarudin, Didin; Rohmah, Siti (UIN Maulana Malik Ibrahim Malang, 2022)
Rituals are sacred religious teachings based on beliefs that will give birth to peace and blessings in the life of the believers. One of them is the Munggahan ritual which is still carried out by the people of Bandung, West Java. This study aimed to determine how the ritual process was carried out and to understand the theological meaning of the Munggahan ritual carried out by the people of Bandung. The design used in this research is descriptive method that systematically explains the facts in the field through the anthropological approach of religion. The data collection process employed observation and interview. The informants were the chairman and several members of the Bandung community. The result shows that the theological meaning of the Munggahan ritual in the month of Ramadan is a form of cleansing oneself from bad things during the past year as well as a form of expression of gratitude for what Allah has given. It also conveys the hope to be given the convenience, safety, health and to avoid bad deeds during worship during Ramadan. Ritual merupakan ajaran agama yang sakral berdasarkan kepercayaan yang akan melahirkan kedamaian dan keberkahan dalam hidup penganutnya. Salah satunya adalah ritual Munggahan yang masih dilakukan oleh masyarakat Bandung, Jawa Barat. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana proses ritual itu dilakukan dan untuk memahami makna teologis dari ritual Munggahan yang dilakukan oleh masyarakat Bandung. Metode yang digunakan dalam penelitian ini adalah metode deskriptif yang menjelaskan secara sistematis fakta-fakta di lapangan melalui pendekatan antropologi agama. Proses pengumpulan data menggunakan observasi dan wawancara. Informan adalah ketua dan beberapa anggota masyarakat Bandung. Hasil penelitian menunjukkan bahwa makna teologis dari ritual Munggahan di bulan Ramadhan adalah sebagai bentuk pembersihan diri dari hal-hal buruk selama satu tahun terakhir sekaligus sebagai bentuk ungkapan rasa syukur atas apa yang telah diberikan oleh Allah SWT. Juga menyampaikan harapan agar diberikan kemudahan, keselamatan, kesehatan dan terhindar dari perbuatan buruk selama beribadah di bulan Ramadhan.